Natural Aporphine Alkaloids with Potential to Impact Metabolic Syndrome - Fei-Xuan Wang; Nan Zhu; Fan Zhou; Dong-Xiang Lin (Molecules, 2021)
The incidence and prevalence of metabolic syndrome has steadily increased worldwide. As a major risk factor for various diseases, metabolic syndrome has come into focus in recent years. Some natural aporphine alkaloids are very promising agents in the prevention and treatment of metabolic syndrome and its components because of their wide variety of biological activities. These natural aporphine alkaloids have protective effects on the different risk factors characterizing metabolic syndrome. In this review, we highlight the activities of bioactive aporphine alkaloids: thaliporphine, boldine, nuciferine, pronuciferine, roemerine, dicentrine, magnoflorine, anonaine, apomorphine, glaucine, predicentrine, isolaureline, xylopine, methylbulbocapnine, and crebanine. We particularly focused on their impact on metabolic syndrome and its components, including insulin resistance and type 2 diabetes mellitus, endothelial dysfunction, hypertension and cardiovascular disease, hyperlipidemia and obesity, non-alcoholic fatty liver disease, hyperuricemia and kidney damage, erectile dysfunction, central nervous system-related disorder, and intestinal microbiota dysbiosis. We also discussed the potential mechanisms of actions by aporphine alkaloids in metabolic syndrome.